PENYELESAIAN WANPRESTASI DALAM PERJANJIAN ENDORSEMENT ANTARA INFLUENCER DAN PELAKU USAHA - Kamilah, Anita; Lananda, Ardelia; Alvian M.S, Ce Kedzma; Rahmah, Mila Arastasya (Jurnal Hukum Ius Publicum, 2025)
Endorsement agreements between influencers and business actors are one form of cooperation that is widely used in the marketing world. However, in its implementation, there are often defaults committed by one of the parties, namely influencers who do not fulfill their obligations in accordance with the provisions agreed upon in the agreement. The purpose of this study is to analyze in more depth the Validity of Endorsement Agreements between Influencers and Business Actors from the Perspective of the Civil Code and the ITE Law, identify Forms of Default in Endorsement Agreements between Influencers and Business Actors, and examine the Mechanism for Settling Defaults in Endorsement Agreements between Influencers and Business Actors Based on the Civil Code and the ITE Law. The method used in this study is the normative legal research method. This research method is carried out by examining problems and processing data obtained from legal regulations in accordance with existing regulations and rules or norms as the basis for research. The results of the study indicate that the settlement of defaults in endorsement agreements between influencers and business actors can be done through litigation or non-litigation. The litigation route takes place through the legal process through the courts, while the non-litigation route takes place through mediation or arbitration.